Disturbed Local Auxin Homeostasis Enhances Cellular Anisotropy and Reveals Alternative Wiring of Auxin-ethylene Crosstalk in Brachypodium distachyon Seminal Roots - Pacheco-Villalobos, David (Public Library of Science, 2013)
Observations gained from model organisms are essential, yet it remains unclear to which degree they are applicable to distant relatives. For example, in the dicotyledon Arabidopsis thaliana (Arabidopsis), auxin biosynthesis via indole-3-pyruvic acid (IPA) is essential for root development and requires redundant TRYPTOPHAN AMINOTRANSFERASE OF ARABIDOPSIS 1 (TAA1) and TAA1-RELATED (TAR) genes. A promoter T-DNA insertion in the monocotyledon Brachypodium distachyon (Brachypodium) TAR2-LIKE gene (BdTAR2L) severely down-regulates expression, suggesting reduced tryptophan aminotransferase activity in this mutant, which thus represents a hypomorphic Bdtar2l allele (Bdtar2l(hypo)). Counterintuitive however, Bdtar2l(hypo) mutants display dramatically elongated seminal roots because of enhanced cell elongation. This phenotype is also observed in another, stronger Bdtar2l allele and can be mimicked by treating wild type with L-kynerunine, a specific TAA1/TAR inhibitor. Surprisingly, L-kynerunine-treated as well as Bdtar2l roots display elevated rather than reduced auxin levels. This does not appear to result from compensation by alternative auxin biosynthesis pathways. Rather, expression of YUCCA genes, which are rate-limiting for conversion of IPA to auxin, is increased in Bdtar2l mutants. Consistent with suppression of Bdtar2l(hypo) root phenotypes upon application of the ethylene precursor 1-aminocyclopropane-1-carboxylic-acid (ACC), BdYUCCA genes are down-regulated upon ACC treatment. Moreover, they are up-regulated in a downstream ethylene-signaling component homolog mutant, Bd ethylene insensitive 2-like 1, which also displays a Bdtar2l root phenotype. In summary, Bdtar2l phenotypes contrast with gradually reduced root growth and auxin levels described for Arabidopsis taa1/tar mutants. This could be explained if in Brachypodium, ethylene inhibits the rate-limiting step of auxin biosynthesis in an IPA-dependent manner to confer auxin levels that are sub-optimal for root cell elongation, as suggested by our observations. Thus, our results reveal a delicate homeostasis of local auxin and ethylene activity to control cell elongation in Brachypodium roots and suggest alternative wiring of auxin-ethylene crosstalk as compared to Arabidopsis.